2012
DOI: 10.2139/ssrn.1992007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of World War II on Economic and Health Outcomes Across Europe

Abstract: We investigate long-run effects of World War II on socioeconomic status and health of older individuals in Europe. We analyze data from SHARELIFE, a retrospective survey conducted as part of SHARE in Europe in 2009. SHARELIFE provides detailed data on events in childhood during and after the war for over 20,000 individuals in 13 European countries. We construct several measures of war exposure-experience of dispossession, persecution, combat in local areas, and hunger periods. Exposure to war and more importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 30 publications
1
70
0
4
Order By: Relevance
“…They can be considered as specific expressions of the general phenomenon of aging, understood as intrinsic, cumulative, 1 Related studies on the impact of childhood hunger on the state of health later in life are Kesternich et al (2016), van den Berg (2016), and Havari and Peracchi (2017). At a more general level, the influence of childhood exposure to World War II on adult health has been investigated by Kesternich et al (2014), Halmdienst and Winter-Ebmer (2014), and Akbulut-Yuksel (2017). A large literature documents the impact of nutrition and disease exposure in childhood on adult height as a health indicator, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They can be considered as specific expressions of the general phenomenon of aging, understood as intrinsic, cumulative, 1 Related studies on the impact of childhood hunger on the state of health later in life are Kesternich et al (2016), van den Berg (2016), and Havari and Peracchi (2017). At a more general level, the influence of childhood exposure to World War II on adult health has been investigated by Kesternich et al (2014), Halmdienst and Winter-Ebmer (2014), and Akbulut-Yuksel (2017). A large literature documents the impact of nutrition and disease exposure in childhood on adult height as a health indicator, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SHARE dataset has been used, for instance, to look at portfolio choices (Christelis et al 2010;, the effect of retirement on cognitive abilities (Rohwedder and Willis 2010;Mazzonna and Peracchi 2012), the effects of education on the distribution of earnings (Brunello et al 2009), the long term economic and health outcomes of exposure to war (Kesternich et al 2012) and the prevalence of informal caregiving to elderly parents (Crespo and Mira 2014). There have also been studies, mostly in gerontology, describing the patterns of volunteering (see Hank and Erlinghagen 2010, for a review) or other outcomes among elderly people.…”
Section: Related Literaturementioning
confidence: 99%
“…The latter is provided in the context of veterans' mental health by random variation in deployment zones (e.g, combat vs. non-combat). When the goal is to investigate mental health in the general population, a similar approach consists of using exogenous variation in war intensity existing across geographical areas, such as the countries (Kesternich et al 2014) or the municipalities (Do and Iyer 2012) where individuals resided during the war. Kesternich et al (2014) found, for instance, that exposure to WWII combats increased the risk of depression for individuals aged 50 or more.…”
Section: Exposure To Violence and Mental Health: A Brief Literature Rmentioning
confidence: 99%
“…When the goal is to investigate mental health in the general population, a similar approach consists of using exogenous variation in war intensity existing across geographical areas, such as the countries (Kesternich et al 2014) or the municipalities (Do and Iyer 2012) where individuals resided during the war. Kesternich et al (2014) found, for instance, that exposure to WWII combats increased the risk of depression for individuals aged 50 or more. Do and Iyer (2012), instead, use the same BiH LSMS data and do not report any significant negative effect of objective measures of war intensity (casualty rates by municipality) on individual mental health (CES-D score).…”
Section: Exposure To Violence and Mental Health: A Brief Literature Rmentioning
confidence: 99%